2011
DOI: 10.1002/pssa.201127309
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence quenching in porous silicon/conjugated polymer composites

Abstract: Phone: þ370 5 2644851, Fax: þ370 5 2627123 MEH-PPV and m-LPPP polymers were spin-coated onto porous silicon (PS). Quenching of the polymer and PS fluorescence has been investigated by means of time-resolved and steady state fluorescence spectroscopy. Decay kinetics of the PS fluorescence in the blue spectral region attributed to the oxidized silicon surface reveals its quenching by the polymer film. No clear evidence of the opposite process, quenching of the polymer fluorescence by PS has been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A sizable “blue shift” (∼10 nm) of the fluorescence maximum has been observed for porous Si as compared to the flat substrate. Similar spectral features were observed for MEH-PPV and other conjugated polymers entrapped in nanoporous structures such as porous silica glass, sol–gel, porous Si, and self-assembly of silica nanospheres . As a rule, the interpretation of the spectral shift was associated with the change of polymer morphology resulting in the existence of isolated chains (suppression of aggregation) inside nanopores similar to a highly diluted solution.…”
Section: Resultsmentioning
confidence: 99%
“…A sizable “blue shift” (∼10 nm) of the fluorescence maximum has been observed for porous Si as compared to the flat substrate. Similar spectral features were observed for MEH-PPV and other conjugated polymers entrapped in nanoporous structures such as porous silica glass, sol–gel, porous Si, and self-assembly of silica nanospheres . As a rule, the interpretation of the spectral shift was associated with the change of polymer morphology resulting in the existence of isolated chains (suppression of aggregation) inside nanopores similar to a highly diluted solution.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work we investigated PS/polymer composites and showed that polymers are responsible for the quenching of the "blue" PS fluorescence [24]. In the current publication we address PS/laser dye composites and energy transfer in these systems.…”
mentioning
confidence: 99%
“…To overcome these problems, polymer-based composites prepared by introducing Si NCs into the polymer matrices have been developed. [18][19][20][21][22] These polymer matrices could chemically stabilize the Si NCs and prevent their aggregation. Signicantly, the composites showed robust photostability, which is suitable for real applications.…”
mentioning
confidence: 99%